Motility of dendritic spines in visual cortex in vivo: Changes during the critical period and effects of visual deprivation - Majewska, Ania (National Academy of Sciences, 2003)
Cortical dendritic spines are highly motile postsynaptic structures onto which most excitatory synapses are formed. It has been postulated that spine dynamics might reflect synaptic plasticity of cortical neurons. To test this hypothesis, we have investigated spine dynamics during the critical period in mouse visual cortex in vivo with and without sensory deprivation. The motility of spines on apical dendrites of layer 5 neurons was assayed by time-lapse two-photon microscopy. Spines were motile at the ages examined, postnatal days (P)21–P42, although motility decreased between P21 and P28 and then remained stable through P42. Binocular deprivation from before the time of eye-opening up-regulated spine motility during the peak of the critical period (P28), without affecting average spine length, class distribution, or density. Deprivation at the start of the critical period had no effect on spine motility, whereas continued deprivation through the end of the critical period appeared to reduce spine motility slightly. We conclude that spine motility might be involved in critical-period plasticity and that reduction of activity during the critical period enhances spine dynamics.